Indonesian Policy on SDGSs: What’s The Top Focus? - Hendrati, Ignatia Martha; Perdana, Putra; Wahed, Mohammad; Asmara, Kiky (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Introduction/Main Objectives: This paper was written to examine the primary objective of the Indonesian government in the SGD's. As of now, the government's efforts to understand SDGs are still in their early stages. It is evident that the implemented policies are not very strict and that the intermediary institutions are still not fully developed. Research Methods: We employ a Systematic Literature Review approach to curate publications from academics and the government in order to examine the government's planning direction. Subsequently, we compare these findings with the Indonesian government's five-year and ten-year Development Plans and juxtapose them with documents issued by local governments. Finding/Results: The research findings indicate that there are differences in emphasis between the central and regional areas in implementing SDGS. Conclusion: Overall, Poverty Reduction and Economic Growth remain the main priorities, followed by Health and Well-being and Quality education. While not all SDGs can be immediately realized, Indonesia is committed to incorporating SDG issues into government policie